(untitled) (Annals of Medical Research, 2023)
Aim: Vitamin D is important in antiproliferative, immunomodulatory, prodifferentiative effects, metabolic functions, and neuromuscular activity. We try to evaluate the relation between vitamin D deficiency and Idiopathic Sudden Sensorineural Hearing Loss (ISSHL) and its impact on response to treatment. Materials and Methods: This study was performed prospectively in 2 groups, 55 participants with SSHL and 55 with normal hearing without middle ear pathology. All patient information such as age, gender, lipid values, coagulation parameters, audiometry results, and vitamin D level was recorded at baseline. Patients with SSHL received steroid therapy at a decreasing dose of 1 mg/kg/day, and their response to treatment had evaluated according to posttreatment audiometry tests. Results: Vitamin D level in the SSHL group with a mean of 17.27±15.73 ng/ml was significantly less than the control group (31.31±27.21 ng/ml; p-value =0.001). The mean pure-tone audiometry (PTA) before treatment was 62.74±23.66 dB HL (range 28-117 dB) and 45.24±23.47 dB HL after treatment (range 6-101 dB HL). The patient group with less vitamin D values was statistically significant than the group with normal vitamin D values in terms of mean PTA before and after treatment (respectively: p=0.010; p=0.002). Pretreatment and posttreatment hearing levels were statistically higher in the group with normal vitamin D. Vitamin D values below 22.16 were a risk factor for sudden hearing loss (p=0.001). Conclusion: In our study, participials with SSHL found a higher vitamin D deficiency level. The role of pathophysiological mechanisms underlying SSHL remains uncertain; vitamin D affecting these mechanisms seems to be an important prognostic factor.